Black Perinatal Mental Health: Prioritizing Maternal Mental Health to Optimize Infant Health and Wellness - Estriplet, Tracey; Morgan, Isabel; Davis, Kelly; Crear Perry, Joia; Matthews, Kay (Frontiers in Psychiatry, 2022)
Infant mental health is interconnected with and affected by maternal mental health. A mother or birthing person's mental health before and during pregnancy and the postpartum period is essential for a child's development. During the first year of life, infants require emotional attachment and bonding to strive. The bond formed during this stage is the foundation in which children develop self-awareness relative to others. Perinatal mood disorders are likely to hinder attachment and are associated with an increased risk of adverse mental health effects for children later in life. The Black community is faced with a crisis as Black mothers experience a higher prevalence of perinatal mood disorders, including postpartum depression and anxiety, compared to the United States national estimates. To better understand the impacts and source of infant mental health, a deeper look into perinatal disparities must continue to be examined. Black mothers and birthing people may often face social and structural barriers that limit their opportunity to interventions and treatment that address the root causes of their perinatal mood disorder. Limited access to resources, lack of universal screening and mental health education, and the disjointed healthcare system serves as barriers, contribute to mental health issues, and put Black mothers and birthing people at a disadvantage in autonomous decision making. The experiences of Black mothers and birthing people in perinatal mental health are crucial to identifying viable solutions. To enhance understanding racial disparities caused by social and structural determinants of health on Black mothers and birthing people's mental health and health care experiences that influence infant mental health, we conducted stakeholder interviews with Black maternal and infant mental health stakeholders. Our study attempted to identify pathways, interventions, and strategies to promote equitable and anti-racist maternal and infant mental health care. Our study concluded that Instituting education on healthy and culturally appropriate ways to support infant development in parent education programs may support Black parents in establishing healthy attachment and bonds. Prioritizing strategies to improve maternal mental health and centering Black parents in developing these educational parenting programs may optimize parenting experiences.